2018
DOI: 10.1002/adma.201706846
|View full text |Cite
|
Sign up to set email alerts
|

Tough and Water‐Insensitive Self‐Healing Elastomer for Robust Electronic Skin

Abstract: An electronic (e-) skin is expected to experience significant wear and tear over time. Therefore, self-healing stretchable materials that are simultaneously soft and with high fracture energy, that is high tolerance of damage or small cracks without propagating, are essential requirements for the realization of robust e-skin. However, previously reported elastomers and especially self-healing polymers are mostly viscoelastic and lack high mechanical toughness. Here, a new class of polymeric material crosslinke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
801
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 902 publications
(867 citation statements)
references
References 40 publications
12
801
1
2
Order By: Relevance
“…By exploiting noncovalent interactions,such as the strong and weak hydrogen bonds holding supramolecular networks together, Kang et al reported that elastomeric strain sensors based on polyurethane-urea can regain ah igh stretchability (g = 500 %) at room temperature after being cut in half (Figure 3e). [141] Hard tissues such as the skeletal bone in vertebrates have open-cell porous structures that house soft tissues and nervous systems.W henabone fracture happens,b oth the hard and the soft components are damaged. In the case of the hard matrix, as eries of cellular and humoral responses will remove debris,h old the bones stationary,a nd remodel the bone.…”
Section: Soft Self-healing Materialsmentioning
confidence: 99%
“…By exploiting noncovalent interactions,such as the strong and weak hydrogen bonds holding supramolecular networks together, Kang et al reported that elastomeric strain sensors based on polyurethane-urea can regain ah igh stretchability (g = 500 %) at room temperature after being cut in half (Figure 3e). [141] Hard tissues such as the skeletal bone in vertebrates have open-cell porous structures that house soft tissues and nervous systems.W henabone fracture happens,b oth the hard and the soft components are damaged. In the case of the hard matrix, as eries of cellular and humoral responses will remove debris,h old the bones stationary,a nd remodel the bone.…”
Section: Soft Self-healing Materialsmentioning
confidence: 99%
“…Moreover, hydrogen bonds can also be established between bidentate urea motifs and monodentate urethane motifs . The strong hydrogen bonding yields elasticity that ensures full recovery from large strains, while the weak hydrogen bonding leads to energy dissipation after breaking and reforming …”
Section: Polymer Compositions Molecular Weights and Polydispersitymentioning
confidence: 99%
“…Devices or strain sensors to provide such a large measure are scarce. More interestingly, enabling these devices with self‐healing soft materials can equip them with recovery and functional restoration after even severe damage, potentially prolonging the service life of these devices . Some self‐healing strain sensors based on rubber, polyurethane composite, and polyborosiloxane have been fabricated by introducing reversible bonds (e.g., hydrogen bond, disulfide bond, and dative bonds) to endow self‐healing capacity to the materials.…”
mentioning
confidence: 99%